Polariton hybridization phenomena on near-field radiative heat transfer in periodic graphene/α-MoO3 cells - Zhang Jihong; Yang Bing; Shi Kezhang; Liu Haotuo; Wu Xiaohu (Nanophotonics)
Coupling of surface plasmon polaritons (SPPs) supported by graphene and hyperbolic phonon polaritons (HPPs) supported by hyperbolic materials (HMs) could effectively promote photon tunneling, and hence the radiative heat transfer. In this work, we investigate the polariton hybridization phenomena on near-field radiative heat transfer (NFRHT) in multilayer heterostructures, which consist of periodic graphene/α-MoO3 cells. Numerical results show that increasing the graphene/α-MoO3 cells can effectively enhance the NFRHT when the vacuum gap is less than 50 nm, but suppresses the enhanced performance with larger gap distance. This depends on the coupling of SPPs and HPPs in the periodic structure, which is analyzed by the energy transmission coefficients distributed in the wavevector space. The influence of the thickness of the α-MoO3 film and the chemical potential of graphene on the NFRHT is investigated. The findings in this work may guide designing high-performance near-field energy transfer and conversion devices based on coupling polaritons.